Designing educational resources of the 21st-century skills instructional models and socio-scientific issues integration - Miza Nina Adlini; Ummi Nur Afinni Dwi Jayanti; Yassir Ni’ma Rangga Wiryawan (Universitas Muhammadiyah Malang, 2024)
This research addresses the limited availability of reference books that comprehensively explain the syntax of the 21st-century learning and socio-scientific issues. It focuses on designing and developing educational resources that integrate the 21st-century skills instructional models with socio-scientific issues, utilizing the 4D (Define, Design, Develop, Disseminate) development model by Thiagarajan (1974). Conducted from March to September 2024 at an Islamic public university in Medan, Sumatera Utara, the subjects were Biology Education students currently enrolled in or who had completed the Biology Learning Strategies course. Data collection involved questionnaires and documentation studies. Initial analysis indicated that students struggled to understand the steps and processes of instructional models supporting the 21st-century skills and socio-scientific issues. To address these challenges, a comprehensive instructional book was developed, emphasizing the 21st-century skills, learning syntax, and socio-scientific issue integration. The book received validation from experts, including a biology learning strategies expert (98.3%), a 21st-century skills expert (100%), and a socio-scientific issues expert (91.7%), all within the highly valid category. It was also deemed highly practical by users, namely students (94.3%) and lecturers (93.7%). The findings underscore the necessity of enhancing learning resources in the course, highlighting the significance of socio-scientific issues in fostering 21st-century skills. This study contributes to advancing learning strategies and offers valuable resources for educators and students preparing for the demands of the 21st-century.